Effectiveness of Tyrosine Kinase Inhibitors on Uncommon Epidermal Growth Factor Receptor Mutations in Non-small Cell Lung Cancer - Xue YANG (Chinese Journal of Lung Cancer, 2015)
Background and objective Epidermal growth factor receptor (EGFR) mutations occur more frequently in non-small cell lung cancer (NSCLC) of women, never smokers, Asian population and those with adenocarcinoma. Short in-frame deletion in exon 19 and L858R substitution are the most common mutations, which are closely associated with EGFR tyrosine kinase inhibitors (TKIs) treatment response. However, the therapeutic effects of EGFR-TKIs on NSCLC with uncommon EGFR mutation subtypes remain unclear. The aim of this study is to investigate the clinicopathologic feature of uncommon EGFR mutations and the outcomes of these patients. Methods Twenty-four patients that harbored uncommon EGFR mutations were included in this study. Clinicopathologic features of uncommon EGFR mutations and the outcomes of these patients were analyzed. Results Of the 24 patients, 13 received EGFR-TKIs treatment. The response rate of EGFR-TKIs treatment was 46.1%, and the median progression-free survival (PFS) was 7.4 months. Mutations on S768I and L861Q composed a major part (8 of 24) of uncommon mutations. Conclusions Uncommon EGFR mutations constituted a unique part of the whole group of EGFR mutations. Their composition and sensitivity to EGFR-TKIs were heterogeneous, which requires further assessment in a prospective study.